(untitled) (Bulletin KNOB, 2003)
As elsewhere in the Netherlands, along the old country roads and waterways at the city entrances Zwolle and Utrecht know suburbs that date back to the Middle Ages. Little is known about the nature of the buildings and - unlike the city centres - hardly any building historical research is being done on this subject. In Utrecht and Amsterdam we found older agricultural buildings in 19th-century urban-development districts. These outlying districts prove to be older and as regards buildings more varied in age than they would seem at first sight. The examples also show that it is risky to say that by now we know what older or younger buildings are to be found in our municipalities. A lot of 20th-century suburbs were built on sites raised with sand, thus eliminating the existing, underlying parcelisation, watercourses, roads, trees and cultural-historical elements. The systematic urban design plan of that time, often presented as ideal, is meanwhile experienced as totalitarian, monotonous as regards design, function and historical diversity. With the recent building of the Utrecht Vinex location Leidse Rijn cultural-historical values were maintained, although the countryside lost its agricultural character. Nevertheless this project presents a major turning point in favour of the ’historical factor’ and diversity. Thrift, anticipating useful elements also characterises the urban extensions of the late Middle Ages through the 19th century. Differentiation in age makes these older and younger districts attractive; there is still something to be discovered and not everything is the same. Analogous to the city centres ’harrowing cases’ and ’missed opportunities’ may occur in these outlying districts now and in the future: unknown heritage should be taken into account there. All this depends greatly on the attitude of those involved, including the authorities. Building-historical research can at any rate help to recognise and map the possibly existing values in time.